Dissociation and interoception in functional neurological disorder. Issue 4 (3rd July 2020) - Pick, Susannah; Rojas-Aguiluz, Maya; Butler, Morgan; Mulrenan, Heather; Nicholson, Timothy R.; Goldstein, Laura H.
ABSTRACT: Introduction: We aimed to examine susceptibility to dissociation and the impact of dissociation on interoceptive processing in individuals with functional neurological disorder (FND). We hypothesised that dissociative states would be elevated and interoceptive accuracy and awareness impaired at baseline in people with FND, and that such differences would be exacerbated following acute dissociation. Methods: Nineteen adults with FND were compared to 20 healthy controls. A modified heart-beat tracking task measured interoceptive accuracy and awareness (confidence) before and after a validated dissociation induction procedure. An exteroceptive processing control task was included. Mann–Whitney tests and r -values (effect size) were computed for between-group comparisons. Results: The FND group displayed elevated dissociation at baseline ( p = 0.001, r = 0.528) compared to controls which increased following dissociation-induction ( p < 0.001, r = 0.663). Interoceptive accuracy did not differ between groups at baseline ( p = 0.967, r = 0.009); however, the FND group had lower accuracy scores post-induction ( p = 0.021, r = 0.379). A negative correlation (trend) between change scores for dissociation and interoceptive accuracy was noted ( rs = −0.411, p = 0.057). Confidence ratings on interoceptive and exteroceptive processing tasks were lower in the FND group ( p -values < 0.05 or <0.01, r -values 0.331–0.489). Conclusions: Individuals with FND experienced greater susceptibility to dissociation, metacognitive deficits and impaired interoceptive accuracy than controls after acute dissociation.